TINGKAT PENERAPAN TEKNOLOGI PENGOLAHAN LIMBAH SAPI MENJADI KOMPOS OLEH PETANI PETERNAK DI DESA MANGESTA, KECAMATAN PENEBEL, KABUPATEN TABANAN - Purba, Luter; Nuraini, K.; Inggriati, Tatik (Jurnal Peternakan Tropika, 2014)
The research on the level of application of cow manure composting technology applied by the farmer had been undertaken from the 1 st December 2010 until 30 th of April 2011. The aim of this research is to set some understandings on how far is farmer could deal with cow’s manure to be composted in the village of Mangesta, district of Penebel, Tabanan Regency. There were some factors of influence the farmers in dealing with the cow’s manure to be compost. Thus the specific aim is to prove on the relationship of some factors such as; knowledge, attitudes, the purpose of processing the cow’s manure to be compost, the amount of cattle they own and the range of area the occupy. The data were collected from two kind of respondents i.e. the farmer group members and not group members. The farmers group member as respondents of this study taken by census method. Each of kinds of respondents has an amount of 20 farmers. Thus, the respondents were 40 farmers. They were all come from the village of Mangesta. The method use to analyze some different factors such as; knowledge, attitude, purpose in relation to how far farmer the farmer deal with the cow’s manure between to the group members and not belong to group members is the method of Wilcoxon’s Rank Sum Test. The methods used examine the relation of some free variables with the level of technology applied by the farmer in dealing with the cow’s feces (Siegel, 1997). The result of the research showed that the level of technology applied between those of group member and those out of the group member has the unreal relations. To Those of group members in deal in relation of some free variables such as; knowledge and purpose of processing the cow’s manure statistically, has a highly (P<0.05) miss the level of cow’s manure composting technology applied by the farmers in the village of Mangesta. However the range of area occupied and amount of cattle owned have a significant relation (P<0.05) with the level of cow manure composting technology applied by the farmers in the village of Mangesta. To those out of the group in relation with variables such as knowledge, attitude, and the purposes together with the range of area owned has a significant relation (P<0.05). Whereas the variables of the amount of cattle owned has a very significant relation (P<0.01) with the level of cow manure composting technology applied by the farmers in the village of Mangesta.
Keywords: The level of technology applied, cow’s manure, compost, and Farmer